Cultura exportadora y competitividad empresarial del acuario San Martin, Iquitos 2023 - Gonzalez Alves Milho, Dulcce Fiorella (2024)
The aim of this thesis was to determine how the export culture relates to the commercial competitiveness of Acuario San Martin company in Iquitos in the year 2023. To address this question, a quantitative approach with a descriptive and explanatory level was employed. The variable "export culture" was analyzed through the review of its dimensions, levels, and categories, based on the perception of the study population. Among the most significant results, there is a Pearson correlation value of 0.946**, indicating a very strong positive correlation. The bilateral sigma value was 0.000, and the calculated p-value was less than 0.05, leading to the acceptance of the hypothesis. Consequently, the hypothesis that "export culture is significantly related to the commercial competitiveness of Acuario San Martin, Iquitos 2023" is confirmed. This finding underscores the importance of fostering a robust export culture as an effective means to enhance the company's competitiveness in the context of exportation in Iquitos in 2023.